(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to create an educational model with tasamuh attitude in a boarding school in Bogor district, with the method of research used is qualitative, while the data collection techniques used are surveys, interviews, documentation, literature studies and data analysis techniques used in this study is to convert quantitative data into qualitative data so that it can be narrated into a conclusion. The result of this research is how to build a model that can be applied throughout the boarding schools in Bogor district, so as to become an educational model with tasamuh attitude in a pesantren.